Green Tea Polyphenols Protect against Acetaminophen-Induced Liver Injury by Regulating the Drug Metabolizing Enzymes and Transporters. (20th November 2020) - Lv, Le; Xu, Chenshu; Mo, Xiaoye; Sun, Hai-Yan; Bi, Huichang
Abstract : Green tea polyphenols (GTPs) have been shown to exhibit diverse beneficial effects against a variety of diseases. Acetaminophen (APAP) overdose is one of the most frequent causes of drug-induced liver injury. In the current study, we aimed to investigate the protective effect of GTP on APAP-induced liver injury in mice and the underlying mechanisms involved. Male C57BL/6J mice were treated orally with different doses of GTP (37.5, 75, or 150 mg/kg) 4 h after APAP overdose (400 mg/kg) and continuously given every 8 h until sacrificed at 4, 12, 20, and 48 h after the first treatment of GTP. Survival rate and histological and biochemical assessments were performed to evaluate the APAP-induced liver injury. Protein expression of multiple drug metabolizing enzymes and transporters was measured to demonstrate the possible mechanisms involved. Our results revealed that administration of different doses of GTP significantly alleviated APAP-induced liver injury by improving the survival rate, hepatocellular necrosis, and ALT/AST/GSH levels after APAP overdose (400 mg/kg). The protein expression of APAP-induced drug transporters and metabolizing enzymes was mostly induced by GTP treatment, which was followed by reduction in drug transporters at the later time points. The current study collectively demonstrated that GTP protects against APAP-induced liver injury, possibly through regulating drug metabolizing enzymes and transporters after APAP overdose.